PROBLEM-BASED LEARNING IN THE TEACHING AND LEARNING OF CALCULUS - Zainal Abidin, Azizan (2008)
Outcome-based education is a system of education that focuses on the product rather than the process. Hence, for two classes of students learning Calculus, they are given the task of working in groups of five to solve a set of application problems that are assigned to them at the onset of the semester. Towards the end of fourteen weeks of study, these students are expected to display their work in a learning portfolio and do a short presentation, describing how the problems are solved. These students are in their second semester of the Foundation Program for Petroleum Engineering and Electrical and Electronic Engineering Degrees. The main purpose of providing the questions at the beginning of their learning process is for them to know clearly the learning outcomes expected of them at the end of the semester. The objective of this research is to describe the implementation of such measuring instruments in the teaching and learning of Calculus which may well be adapted by teachers or lecturers teaching Mathematics in secondary schools or institutions of higher learning. This technique may also be recommended as an alternative to the traditional pencil and paper method of assessment in the teaching of Mathematics. The learning reflections described by the students involved in the study not only show the enjoyment that they value but also contribute to motivate their peers as well as the facilitators in their learning process.